Ideological Views of Islam in Relation to Contemporary Human Rights: An Evaluation - Karim, Sheikh Mohammad Towhidul; Murad, Mohammad Hasan (IIUC Studies, 2014)
Islam, being the religion of nature, embodies all the basic ideas of human rights. The principles of human rights were introduced during the advent of Islam in order to ensure peace, justice, tranquility, morality, dignity, quality and values all over the world. The rights recognized by Islam were established not only to protect special race like Muslims, but also to shelter the non-Muslims. This research is mainly based on secondary data and logic. This article is an attempt to outline the contribution of Islam in the field of human rights and endeavors to establish that the principles of human rights are not the sole outcome of the progress of western civilization. DOI: http://dx.doi.org/10.3329/iiucs.v8i0.20406 IIUC Studies Vol.8 December 2011: 113-130